Analysis of the Application of the Mini Story Theater Learning Model (TMK), Story Poster Making (PPK), and Lectures (CPM) in Islamic Religious Education Learning - Nurul Azizatul Isnaini; Adam Malik; Rahayu Kariadinata (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to analyze the application of the Mini Story Theater (TMK) learning model, Making Story Posters (PPK), and Lectures (CPM) in learning Islamic Religious Education. This study uses a quantitative approach with quasi-experimental methods. The research population consisted of all 92 students in class VII junior high school, with a sample of three classes randomly selected using the cluster random sampling technique, class VII A as the experimental group 1 with the treatment of the Theater Mini Story or TMK learning model; class VII B as the experimental group 2 was treated with the learning model Making Story Posters or PPK; and class VII C as the control group was given the learning model of Lecture Delivery of Materials or CPM. The research instruments used were questionnaires and interviews. The research data were analyzed using the analysis of variance technique (ANOVA) one-line testing of more than two samples using SPSS 26. The results revealed that there were no differences in students' understanding of the Acts of the Prophets and Apostles (KNR) in PAI subjects between students using the learning model Story Mini Theater (TMK), Story Poster Making (PPK), and Lectures (CPM).